Non-aqueous electrolyte secondary battery

JP7626131B2Active Publication Date: 2025-02-04TORAY INDUSTRIES INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022521101
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-31
Filing Date
2022-03-29
Publication Date
2025-02-04
Estimated Expiration
2042-03-29

AI Technical Summary

Benefits of technology

【0019】 本発明によれば、非水電解液が異なる2種類の溶媒を含む非水電解液二次電池が提供される。また、異なる2種類の非水電解液をセパレータで分離することができるポリマー膜が得られる。これにより、本発明のポリマー膜をセパレータに用いて構成された非水電解液二次電池は、セパレータの耐熱性が良好で安全性が高く、電池電圧が高い、つまり高電圧·高容量の非水電解液二次電池を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626131000001
    Figure 0007626131000001
  • Figure 0007626131000002
    Figure 0007626131000002
  • Figure 0007626131000003
    Figure 0007626131000003
Patent Text Reader

Abstract

The purpose of the present invention is to provide a non-aqueous electrolyte secondary battery having high stability and a high battery voltage. To this end, provided is a non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, a non-aqueous electrolyte, and a separator, wherein: the active material of the positive electrode is a lithium-containing transition metal oxide represented by the general formula LixMyOz (M being at least one kind of element selected from the group consisting of Ni, Co, Mn, Al, Mg, and Mo, and the composition ratio satisfying 0.8≤x≤1.3, 0.5≤y≤2, 1≤z≤4); the active material of the negative electrode comprises metallic lithium or at least one compound selected from the group consisting of a C-based compound, an Si-based compound, an Sn-based compound, and metallic lithium; the non-aqueous electrolyte comprises two kinds of solvent, is separated by the separator, and the composition thereof coming into contact with the negative electrode side and the composition thereof coming into contact with the positive electrode side are different; and the separator is a polymeric film having an air resistance of more than 10000 seconds, an ionic conductance of at least 1x10-5S / cm, and the contact angle between at least one surface of the separator and an organic solvent is at least 90°.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a non-aqueous electrolyte secondary battery. [Background technology]

[0002] 2. Description of the Related Art Nonaqueous electrolyte secondary batteries such as lithium-ion batteries are widely used in a variety of applications, including portable digital devices such as smartphones, tablets, mobile phones, laptops, digital cameras, digital video cameras, and portable game consoles; portable devices such as power tools, electric motorcycles, and electrically assisted bicycles; and automotive applications such as electric vehicles, hybrid vehicles, and plug-in hybrid vehicles.

[0003] A non-aqueous electrolyte secondary battery generally has a configuration in which a separator and a non-aqueous electrolyte are interposed between a positive electrode in which a positive electrode active material is laminated on a current collector and a negative electrode in which a negative electrode active material is laminated on a current collector.

[0004] Polyolefin-based porous substrates are generally used as separators. The separators are required to have the following characteristics: a porous structure that contains an electrolyte and allows ion migration; and a shutdown characteristic that, when a nonaqueous electrolyte secondary battery generates abnormal heat, melts the porous structure and closes it, stopping ion migration and thus stopping the function of the battery.

[0005] However, in recent years, there has been a demand for even higher energy density in non-aqueous electrolyte secondary batteries, and in particular, studies have begun on increasing the capacity of positive and negative electrode active materials as well as increasing the voltage to improve the electromotive force of the battery.

[0006] The oxidation resistance and reduction resistance of the solvent that forms the non-aqueous electrolyte are important for increasing the voltage of the battery. The oxidation resistance and reduction resistance of the solvent can be evaluated by the highest occupied molecular orbital (HOMO) energy and the lowest unoccupied molecular orbital (LUMO) energy according to the frontier orbital theory. The oxidizing property of the solvent can be organized by the HOMO energy, and the more the absolute value of the HOMO energy is negative, the more difficult it is to oxidize. On the other hand, the reducing property of the non-aqueous electrolyte can be organized by the LUMO energy, and the more the absolute value of the LUMO energy is positive, the more difficult it is to reduce. However, a solvent with a large absolute value of the HOMO energy on the negative side does not have a large absolute value of the LUMO energy on the positive side. Therefore, due to the balance between the oxidation resistance and reduction resistance of the solvent, the battery voltage cannot be substantially increased to 4.5V or more.

[0007] Therefore, it is important to solve the problems of the non-aqueous electrolyte by using two different types of non-aqueous electrolyte in combination. As an approach to using two different types of non-aqueous electrolyte in combination, Patent Documents 1 and 2 propose improving battery characteristics by arranging different polymer electrolytes on the positive electrode side and the negative electrode side.

[0008] In addition, since the energy of a battery increases as the battery voltage increases, the heat resistance of the separator also becomes important. Patent Document 3 proposes providing a porous layer containing a heat-resistant resin to impart heat resistance to the separator. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2002-319434 A [Patent Document 2] JP 2002-42874 A [Patent Document 3] International Publication No. 2018 / 155287 Summary of the Invention [Problem to be solved by the invention]

[0010] However, Patent Documents 1 and 2 use different polymer electrolyte layers on the positive and negative electrode sides, but the polymer electrolyte layer is a gel polymer, and since the polymer electrolyte layer swells with the electrolyte solution, the different electrolyte solutions on the positive and negative electrode sides cannot be sufficiently separated. In other words, electrolyte solutions of two different compositions cannot be used together, and it is not possible to achieve high voltage and high capacity batteries.

[0011] The battery in Patent Document 3 has high heat resistance and improves the safety of the battery. However, since the membrane is porous, if nonaqueous electrolytes of two different compositions are used, the two types of nonaqueous electrolytes will mix together, making it impossible to achieve a high-voltage and high-capacity battery.

[0012] Therefore, in view of the above problems, an object of the present invention is to provide a nonaqueous electrolyte secondary battery that is highly safe and has a high battery voltage by using a separator that has heat resistance to membrane rupture, i.e., a high membrane meltdown temperature, and is capable of separating two different types of electrolyte in a battery that uses nonaqueous electrolytes having two different solvent compositions. [Means for solving the problem]

[0013] In order to solve the above problems, the nonaqueous electrolyte secondary battery of the present invention has the following configuration. (1) A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, a non-aqueous electrolyte, and a separator, the positive electrode active material being represented by the general formula LixMyOz (M is at least one element selected from the group consisting of Ni, Co, Mn, Al, Mg, and Mo, and the composition ratios satisfy 0.8≦x≦1.3, 0.5≦y≦2, and 1≦z≦4). 。 the negative electrode active material contains one or more compounds selected from the group consisting of C-based compounds, Si-based compounds, Sn-based compounds, and metallic lithium, or metallic lithium; the nonaqueous electrolyte contains two types of solvents and is separated by the separator; the composition of the nonaqueous electrolyte in contact with the negative electrode side is different from the composition of the nonaqueous electrolyte in contact with the positive electrode side; the nonaqueous electrolyte contains a solvent and an electrolyte, the solvent of the nonaqueous electrolyte in contact with the positive electrode side has a HOMO energy of −11.5 eV or less, and the solvent of the nonaqueous electrolyte in contact with the negative electrode side has a LUMO energy of 2.0 eV or more,The separator has an air permeability of more than 10,000 seconds and an ionic conductivity of 1×10 -5 S / cm or more, and further, the contact angle between at least one surface of the separator and an organic solvent is 90° or more.

[0014] (2) The separator has an air permeability of more than 10,000 seconds and an ionic conductivity of 1×10 -5 S / cm or more, and further, the contact angle between at least one surface of the separator and a propylene carbonate liquid and a 1,2-dimethoxyethane liquid is 90° or more.

[0015] (3 )

[0016] (4) The nonaqueous electrolyte secondary battery according to any one of (1) to (3), wherein the rate of change in the contact angle of the polymer film with an organic solvent after one hour is less than 10%.

[0017] (5) The nonaqueous electrolyte secondary battery according to any one of (1) to (4), wherein the rate of change in the contact angle of the polymer film with a propylene carbonate liquid and a 1,2-dimethoxyethane liquid after one hour is less than 10%.

[0018] (6) The nonaqueous electrolyte secondary battery according to any one of (1) to (5), wherein the polymer film has an areal heat shrinkage rate of 10% or less after heat treatment at 180° C. for 60 minutes. (7) The nonaqueous electrolyte secondary battery according to any one of (1) to (6), wherein the polymer film has a meltdown temperature of 300° C. or higher. (8) The nonaqueous electrolyte secondary battery according to any one of (1) to (7), wherein the polymer film contains at least one polymer selected from the group consisting of aromatic polyamides, aromatic polyimides, and aromatic polyamideimides. Effect of the Invention

[0019] According to the present invention, a nonaqueous electrolyte secondary battery is provided in which the nonaqueous electrolyte contains two different types of solvent. Also, a polymer membrane capable of separating two different types of nonaqueous electrolyte with a separator is obtained. As a result, a nonaqueous electrolyte secondary battery constructed using the polymer membrane of the present invention as a separator has a good heat resistance of the separator, is highly safe, and has a high battery voltage, i.e., a high-voltage, high-capacity nonaqueous electrolyte secondary battery can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The nonaqueous electrolyte secondary battery according to an embodiment of the present invention will be described in detail below. A nonaqueous electrolyte secondary battery according to an embodiment of the present invention is a nonaqueous electrolyte secondary battery including a positive electrode, a negative electrode, a nonaqueous electrolyte, and a separator, in which an active material of the positive electrode is a lithium-containing transition metal oxide represented by a general formula LixMyOz (M is at least one element selected from the group consisting of Ni, Co, Mn, Al, Mg, and Mo, and the composition ratio satisfies 0.8≦x≦1.3, 0.5≦y≦2, and 1≦z≦4), an active material of the negative electrode includes one or more compounds selected from the group consisting of C-based compounds, Si-based compounds, Sn-based compounds, and metallic lithium, or metallic lithium, the nonaqueous electrolyte has different solvent compositions on the negative electrode side and the positive electrode side, and the separator has an air permeability of more than 10,000 seconds and an ionic conductivity of 1×10 -5 The polymer membrane has a surface area of ​​1.5 S / cm or more and a contact angle of an organic solvent of 90° or more. As the organic solvent, a propylene carbonate solution and a 1,2-dimethoxyethane solution are preferably used.

[0021] The nonaqueous electrolyte of the present invention has different solvent compositions on the negative electrode side and the positive electrode side, which means that the nonaqueous electrolyte contains two types of solvents and is separated by the separator, and the solvent of the nonaqueous electrolyte in contact with the negative electrode side has a different composition from the solvent of the nonaqueous electrolyte in contact with the positive electrode side.

[0022] The components, that is, the positive electrode, the negative electrode, the non-aqueous electrolyte, and the separator, will be described in detail below.

[0023] [Positive electrode] The positive electrode includes a positive electrode current collector and a positive electrode mixture layer formed on the positive electrode current collector. The positive electrode current collector may be made of, for example, aluminum, an aluminum alloy, stainless steel, etc. The positive electrode mixture layer includes a positive electrode active material and a binder.

[0024] In an embodiment of the present invention, the positive electrode active material is a lithium-containing transition metal oxide represented by the general formula LixMyOz (M is at least one element selected from the group consisting of Ni, Co, Mn, Al, Mg, and Mo. The composition ratio satisfies 0.8≦x≦1.3, 0.5≦y≦2, and 1≦z≦4), and examples of such oxides include LiCoO2, LiMn2O4, and Li(Ni 0.5 Co 0.2 Mn 0.3 )O2, Li(Ni 0.8 Co 0.1 Mn 0.1 )O2, Li(Ni 0.9 Co 0.1 )O2, LiNiO2, Li(Ni 0.9 Co 0.05 Mn 0.025 Mg 0.025 )O2, Li(Ni 0.9 Co 0.05 Al 0.05 )O2, Li(Ni 0.8 Co 0.1 Mn 0.08 Al 0.01 Mg 0.01 )O2, Li(Ni 0.8 Co 0.1 Mn 0.08 Mo 0.02 )O2, etc.

[0025] The positive electrode is manufactured, for example, as follows. A positive electrode active material is mixed with a conductive agent such as graphite or carbon black and a binder such as polyvinylidene fluoride to form a positive electrode mixture. This positive electrode mixture is then dispersed in a solvent such as N-methyl-2-pyrrolidone (NMP) to form a slurry. This is applied to both sides of a positive electrode current collector, and after the solvent is dried, the mixture is compressed and smoothed by a roll press or the like to manufacture the positive electrode.

[0026] [Negative electrode] The negative electrode includes a negative electrode current collector and a negative electrode mixture layer formed on the negative electrode current collector. As the negative electrode current collector, for example, a negative electrode current collector made of copper, nickel, or stainless steel can be used. The negative electrode mixture layer has a structure including a negative electrode active material and a binder.

[0027] In an embodiment of the present invention, the negative electrode active material contains one or more compounds selected from the group consisting of C-based compounds, Si-based compounds, Sn-based compounds, metallic lithium, or metallic lithium. Each compound may be used alone, or a plurality of compounds may be used in combination.

[0028] Examples of the Sn-based compound include Sn, SnO2, Sn-R (wherein R is an alkali metal, alkaline earth metal, Group 13 to Group 16 element, transition metal, rare earth element, or a combination thereof, provided that Sn is excluded), and the like.

[0029] Examples of the Si-based compound include Si, SiOx (0 < x < 2), Si-C composite, Si-Q alloy (wherein Q is an element selected from alkali metals, alkaline earth metals, elements selected from Group 13 to Group 16 (elements selected from elements belonging to Group 13 to Group 16 of the periodic table), provided that Si is excluded, transition metals, rare earth elements, and combinations thereof).

[0030] Here, as the specific elements of Q or R in the Si-Q and Sn-R, one selected from Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ti, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof may be used. Among these, the Si-based compound is preferred, and more preferably, SiOx (0 < x < 2).

[0031] Examples of the C-based compound include artificial graphite, natural graphite, hard carbon, soft carbon, etc. The C-based compound may be used in combination with a Si-based compound or a Sn-based compound.

[0032] The negative electrode is manufactured, for example, as follows. A negative electrode active material containing at least one of a C-based compound, a Si-based compound, and a Sn-based compound is mixed with a binder such as a styrene-butadiene copolymer, a polyimide, a polyamideimide, or a polyvinylidene fluoride to form a negative electrode mixture. This negative electrode mixture is then dispersed in a solvent such as N-methyl-2-pyrrolidone (NMP) or water to form a slurry. This is applied to both sides of a negative electrode current collector, and after the solvent is dried, the mixture is compressed and smoothed by a roll press or the like to manufacture a negative electrode.

[0033] If necessary, a negative electrode conductive assistant may be used. Examples of the negative electrode conductive assistant include acetylene black, ketjen black, carbon nanotubes, fullerene, graphene, and carbon fiber.

[0034] When the negative electrode active material is metallic lithium, it can be used to form the negative electrode alone, and can be produced by generating lithium nanoparticles on the negative electrode current collector using the gas deposition method and spraying and depositing them together with He gas. Metallic lithium can also be used to form a layered structure with a C-based compound.

[0035] [Nonaqueous electrolyte] The nonaqueous electrolyte is composed of a solvent and an electrolyte. The nonaqueous electrolyte used in the embodiment of the present invention uses a nonaqueous electrolyte having different solvents on the negative electrode side and the positive electrode side. That is, the nonaqueous electrolyte contains two types of solvents, and the composition of the nonaqueous electrolyte in contact with the negative electrode side is different from that of the nonaqueous electrolyte in contact with the positive electrode side. The nonaqueous electrolytes with different compositions include nonaqueous electrolytes with different solvent compositions.

[0036] As the above-mentioned solvent, cyclic esters, chain esters, cyclic ethers, chain ethers, amides, etc. are used. Specifically, ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), γ-butyrolactone (γBL), 2-methyl-γ-butyrolactone, acetyl-γ-butyrolactone, γ-valerolactone, 1,2-dimethoxyethane (DME), 1,2-ethoxyethane, diethyl ether, ethylene glycol dialkyl ether, diethylene glycol dialkyl ether, triethylene glycol dialkyl ether, tetraethylene glycol dialkyl ether, dipropyl carbonate, methyl butyl carbonate, methyl ... Organic solvents such as pyrcarbonate, ethyl butyl carbonate, ethyl propyl carbonate, butyl propyl carbonate, alkyl propionates, dialkyl malonates, alkyl acetates, tetrahydrofuran (THF), alkyl tetrahydrofurans, dialkyl alkyl tetrahydrofurans, alkoxy tetrahydrofurans, dialkoxy tetrahydrofurans, 1,3-dioxolane, alkyl-1,3-dioxolane, 1,4-dioxolane, 2-methyl tetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, methyl propionate, ethyl propionate, phosphoric acid triesters, and N-methyl-2-pyrrolidone, as well as derivatives and mixtures thereof, are preferably used.

[0037] When using the above-mentioned solvents as electrolytes, the important factors are the oxidation resistance and reduction resistance of the solvent, which can be evaluated by the highest occupied molecular orbital (HOMO) energy and the lowest unoccupied molecular orbital (LUMO) energy according to frontier orbital theory.

[0038] Solvents with a HOMO energy of -11.5 eV or less include cyclic esters and chain esters. Solvents with a HOMO energy of -11.5 eV or less have excellent oxidation resistance, but have low LUMO energy and low reduction resistance. On the other hand, solvents with a LUMO energy of 2 eV or more include cyclic ethers, chain ethers, and amides. Solvents with a LUMO energy of 2.0 eV or more have excellent reduction resistance, but have high HOMO energy and low oxidation resistance. In other words, there is no solvent that has both high oxidation resistance and high reduction resistance.

[0039] In the present invention, two types of solvents, one with excellent oxidation resistance and the other with excellent reduction resistance, are used as the solvent for the nonaqueous electrolyte, and the two different types of nonaqueous electrolytes are separated by a separator so as not to mix together to form a nonaqueous electrolyte. At this time, two types of nonaqueous electrolytes are used: one with a HOMO energy of -11.5 eV or less and one with a LUMO energy of 2.0 eV or more.

[0040] The arrangement of the two types of nonaqueous electrolytes is preferably such that the nonaqueous electrolyte whose solvent has a HOMO energy of -11.5 eV or less is arranged on the positive electrode side, and the nonaqueous electrolyte whose solvent has a LUMO energy of 2.0 eV or more is arranged on the negative electrode side. In this way, the two types of nonaqueous electrolytes are separated by a separator so as not to mix and arranged on the positive electrode side and the negative electrode side, thereby achieving a high voltage battery. Note that the lower limit of the HOMO energy of the solvent constituting the nonaqueous electrolyte in contact with the positive electrode side is preferably as large as the absolute value, since the HOMO energy is a negative value. The upper limit of the LOMO energy of the solvent constituting the nonaqueous electrolyte in contact with the negative electrode side is preferably as large as the LOMO energy.

[0041] As the electrolyte contained in the non-aqueous electrolyte, alkali metals, particularly lithium halides, perchlorates, thiocyanates, boron fluorides, phosphorus fluorides, arsenic fluorides, aluminum fluorides, trifluoromethyl sulfates, etc. are preferably used. For example, one or more salts such as lithium salts (electrolytes) such as lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenic (LiAsF6), lithium trifluoromethasulfonate (LiCF3SO3), and lithium bistrifluoromethylsulfonylimide [LiN(CF3SO2)2] can be used, but lithium hexafluorophosphate is preferred from the viewpoint of oxidation resistance and reduction resistance.

[0042] The amount of electrolyte dissolved in the non-aqueous solvent is preferably 0.5 to 3.0 mol / L, and particularly preferably 0.8 to 1.5 mol / L. The electrolytes contained in the two types of non-aqueous electrolytic solutions may be the same or different.

[0043] If necessary, the non-aqueous electrolyte may contain other additives, such as vinylene carbonate, fluoroethylene carbonate, ethylene sulfite, 1,4-butane sultone, propane sultone, 2,4-difluoroanisole, biphenyl, cyclohexylbenzene, and the like.

[0044] [Separator] The separator in the present invention has an air permeability of more than 10,000 seconds, a contact angle with an organic solvent of 90° or more, and an ionic conductivity of 1×10 -5 It is a polymer membrane with a hardness of 1.0 S / cm or more.

[0045] When the polymer membrane has an air permeability of more than 10,000 seconds, it can separate two different nonaqueous electrolytes in a battery. When the air permeability is more than 10,000 seconds, the separator can be considered to have a nonporous structure with substantially no continuous pores.

[0046] The polymer membrane can separate two kinds of nonaqueous electrolytes because the contact angle with the organic solvent is 90° or more, and the polymer membrane does not swell with the nonaqueous electrolyte and the nonaqueous electrolyte does not penetrate the polymer membrane. According to the findings of the present inventors, the contact angle with the solution tends to be large in the microporous membrane used for the separator due to the influence of the surface structure of the micropores, but the polymer membrane that separates the two different nonaqueous electrolytes so that they do not mix has a non-porous structure, so the contact angle tends to be small. Depending on the combination of the polymer membrane and the organic solvent, the contact angle becomes less than 90°, and the polymer membrane becomes wet with the solvent, which reduces the high voltage. The decrease in battery voltage and battery capacity can be evaluated by performing a cycle test in which charging and discharging are repeated.

[0047] In addition, from the viewpoint of being able to separate the electrolyte when the battery is used and maintaining the battery characteristics, it is preferable that the polymer film of the separator is not wetted with an organic solvent for a long time. Therefore, it is preferable that the change rate of the contact angle of the polymer film with the organic solvent after 1 hour is less than 10%, more preferably less than 7%. The contact angle is evaluated for each of a solvent with a HOMO energy of -11.5 eV or less and a solvent with a LUMO energy of 2.0 eV or more. Specifically, propylene carbonate can be used as a solvent with a HOMO energy of -11.5 eV or less, and 1,2-dimethoxyethane can be used as a solvent with a LUMO energy of 2.0 eV or more.

[0048] The polymer membrane has an ionic conductivity of 1×10 -5 Since the polymer membrane has a non-porous structure, it cannot be impregnated with an electrolyte and the electrolyte does not swell, so it is important from the viewpoint of battery characteristics that the polymer membrane has ionic conductivity.

[0049] Furthermore, the polymer film is required to have heat resistance, and from the viewpoint of battery safety, the areal thermal shrinkage rate after heating at 180°C for 60 minutes is preferably 10% or less, more preferably 5% or less. In particular, when metallic lithium is used for the negative electrode, the spontaneous ignition temperature of metallic lithium is 179°C, and it is important from the viewpoint of battery safety that the thermal shrinkage rate at or above the spontaneous ignition temperature is small.

[0050] From the viewpoint of battery safety, the meltdown temperature of the polymer film is preferably 300° C. or higher, and more preferably 350° C. or higher.

[0051] The polymer membrane that achieves the above separator will be described below.

[0052] As the polymer constituting the polymer membrane as the separator, a polymer having an aromatic ring on the main chain is suitable as a polymer that has both heat resistance, strength, and flexibility. Examples of such polymers include aromatic polyamide (aramid), aromatic polyimide, aromatic polyamideimide, aromatic polyether ketone, aromatic polyether ether ketone, aromatic polyarylate, aromatic polysulfone, aromatic polyether sulfone, aromatic polyether imide, aromatic polycarbonate, etc. Also, a blend of multiple polymers may be used. Among them, it is preferable that the polymer membrane contains at least one polymer selected from the group consisting of aromatic polyamide, aromatic polyimide, and aromatic polyamideimide, since it has excellent heat resistance and is easy to maintain high strength when thinned. It is preferable that the polymer membrane contains at least one polymer selected from the group consisting of aromatic polyamide, aromatic polyimide, and aromatic polyamideimide in 30 to 100 mass % of the entire polymer membrane, more preferably 50 to 100 mass %.

[0053] As a polymer that can be suitably used in the present invention, it is preferable that the polymer constituting the membrane contains a polymer having a structure represented by any one of the following chemical formulas (I) to (III). Examples of aromatic polyamides include polymers having a repeating unit represented by the following chemical formula (I), aromatic polyimides include polymers having a repeating unit represented by the following chemical formula (II), and aromatic polyamideimides include polymers having a repeating unit represented by the following chemical formula (III).

[0054] [ka]

[0055] [ka]

[0056] [ka]

[0057] Here, Ar1 and / or Ar2 in the chemical formulas (I) to (III) are aromatic groups, and each may be a single group or a multi-component copolymer with multiple groups. In addition, the bonds constituting the main chain on the aromatic ring may be either meta-oriented or para-oriented. Furthermore, some of the hydrogen atoms on the aromatic ring may be substituted with any group.

[0058] In the present invention, one method for achieving both separation of the electrolyte solution, heat resistance, and excellent ion conductivity is to transport ions by hopping by controlling the polarity of the polymer.

[0059] In the present invention, when aromatic polyamide (including aromatic polyamic acid), aromatic polyimide or aromatic polyamideimide is used, since it has a carbonyl group in the structure, this generally becomes a site with high affinity for lithium ions. Therefore, in order for lithium ions to move in the polymer film, a site with lower affinity for lithium ions than the carbonyl group is required, so it is preferable to have an ether bond or a thioether bond in the main chain or side chain (in the main chain or on the side chain).

[0060] More preferably, the main chain has an ether bond, or the aromatic ring has at least one of a carboxylic acid group, a carboxylate group, a sulfonic acid group, a sulfonate group, an alkoxy group, and a cyanate group as a substituent.More preferably, 25 to 100 mol % of the total of all groups in Ar1 and Ar2 in chemical formulas (I) to (III) is at least one group selected from the groups represented by the following chemical formulas (IV) to (VI), and the above ratio is more preferably 50 to 100 mol %.

[0061] [ka]

[0062] (The double dashed lines in chemical formulas (IV) to (VI) represent one or two bonds.) Here, some of the hydrogen atoms on the aromatic rings of chemical formulas (IV) to (VI) may be substituted with any group, such as a halogen group such as fluorine, bromine, or chlorine, a nitro group, a cyano group, an alkyl group such as methyl, ethyl, or propyl, an alkoxy group such as methoxy, ethoxy, or propoxy, or a carboxylic acid group.

[0063] In addition, it is preferable to add a lithium salt to facilitate ion conduction in the polymer film, and it is even more preferable to add a lithium salt with a large anion radius and high dissociation property of lithium ions to further improve ion conductivity. Here, the lithium salt to be added can be the same as the solute contained in the electrolyte. Among them, lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethasulfonate (LiCF3SO3), and lithium bistrifluoromethylsulfonylimide [LiN(CF3SO2)2] are preferable, and from the viewpoint of anion radius and dissociation property of lithium ions, the addition of lithium trifluoromethasulfonate (LiCF3SO3) and lithium bistrifluoromethylsulfonylimide [LiN(CF3SO2)2] is preferable.

[0064] Next, a method for producing the polymer membrane that serves as the separator will be described below.

[0065] [Synthesis of polymer for separator] First, a method for obtaining a polymer that can be used in the polymer film of the present invention will be described using aromatic polyamide and aromatic polyimide as examples. Of course, the polymer and the polymerization method that can be used in the present invention are not limited to these.

[0066] Various methods are available for obtaining aromatic polyamides, but for example, when using low-temperature solution polymerization with acid dichloride and diamine as raw materials, they are synthesized in aprotic organic polar solvents such as N-methylpyrrolidone, N,N-dimethylacetamide, dimethylformamide, dimethylsulfoxide, etc. In the case of solution polymerization, in order to obtain a polymer with a high molecular weight, it is preferable that the water content of the solvent used in polymerization is 500 ppm or less (based on mass, the same applies below), and more preferably 200 ppm or less.

[0067] A method for obtaining aromatic polyimides or their precursors, aromatic polyamic acids, can be, for example, a method of synthesis by solution polymerization in an aprotic organic polar solvent using tetracarboxylic anhydride and aromatic diamine as raw materials, etc. Examples of the aprotic organic polar solvent include N-methyl-2-pyrrolidone, N,N-dimethylacetamide, dimethylformamide, and dimethylsulfoxide.

[0068] When the raw materials, tetracarboxylic anhydride and aromatic diamine, are used in equal amounts, an ultra-high molecular weight polymer may be produced, so it is preferable to adjust the molar ratio of one to 90.0 to 99.5 mol % of the other.

[0069] The logarithmic viscosity (ηinh) of the aromatic polyamide, aromatic polyimide or its precursor, aromatic polyamic acid, is preferably 0.5 to 6.0 dl / g. If the logarithmic viscosity is less than 0.5 dl / g, the binding strength between the chains due to the entanglement of the polymer molecular chains is reduced, so that mechanical properties such as toughness and strength may decrease, or the heat shrinkage rate may increase. If the logarithmic viscosity exceeds 6.0 dl / g, the ion permeability may decrease.

[0070] [Preparation of film-forming materials] Next, the membrane-forming stock solution (hereinafter, sometimes simply referred to as membrane-forming stock solution) used in the process for producing the polymer membrane of the present invention will be described.

[0071] As the membrane forming solution, the polymer solution after polymerization may be used as it is, or the polymer may be isolated and then redissolved in the above-mentioned aprotic organic polar solvent or an inorganic solvent such as sulfuric acid before use.

[0072] The concentration of the polymer in the film-forming solution is preferably 3 to 30% by mass, more preferably 5 to 20% by mass. The above-mentioned lithium salt is preferably added to the film-forming solution from the viewpoint of improving ion conductivity. The amount of the lithium salt added is preferably such that the molar ratio of lithium in the lithium salt to oxygen in the polymer is 0.1 or more, more preferably 0.2 or more.

[0073] [Production of polymer membranes for separators] Next, a method for forming the polymer membrane of the present invention will be described. The membrane forming solution prepared as above can be used for membrane formation by a so-called solution membrane formation method. The solution membrane formation method includes a dry-wet method, a dry method, a wet method, etc., and any method may be used for membrane formation, but here, the dry-wet method will be described as an example. The polymer membrane of the present invention may be formed directly on a substrate or an electrode having voids to form a laminated composite, but here, a method for forming the polymer membrane as a single film will be described.

[0074] When forming a film by a dry-wet method, the film forming solution is extruded from a die onto a support such as a drum, an endless belt, or a film to form a film, and then the film is dried until it has self-supporting properties. The drying conditions are, for example, 60 to 220°C and 60 minutes or less. However, when a polyamic acid polymer is used to obtain a film made of aromatic polyamic acid without imidization, the drying temperature is preferably 60 to 150°C, more preferably 60 to 120°C.

[0075] The film after the dry process is peeled off from the support and introduced into the wet process, where it is desalted, desolvated, and further stretched, dried, and heat-treated. The stretching ratio is preferably in the range of 0.8 to 8.0 in area ratio (area ratio is defined as the value obtained by dividing the area of ​​the film after stretching by the area of ​​the film before stretching. A ratio of 1 or less means relaxation), and more preferably 1.0 to 5.0. The heat treatment is performed at a temperature of 80°C to 500°C, preferably 150°C to 400°C, for several seconds to several tens of minutes. However, when a polyamic acid polymer is used and a film made of polyamic acid is to be obtained without imidization, the heat treatment temperature is preferably 80 to 150°C. More preferably, the heat treatment temperature is 80 to 120°C under reduced pressure.

[0076] [Nonaqueous electrolyte secondary battery] Examples of the form of the nonaqueous electrolyte secondary battery of this embodiment include a coin battery, a laminate battery, a cylindrical battery, a square battery, etc. For increasing the capacity of the battery or for modularizing a plurality of batteries by connecting them together, a laminate battery, a cylindrical battery, and a square battery are particularly preferable.

[0077] As a method for producing a nonaqueous electrolyte secondary battery, for example, in the case of a laminated battery, a cylindrical battery, or a prismatic battery, a positive electrode sheet, a separator, a negative electrode sheet, and a separator are stacked in this order and wound into a spiral shape to produce a wound body, and in the case of a coin battery, a laminated battery, or a prismatic battery, a positive electrode sheet, a separator, a negative electrode sheet, and a separator of a predetermined size are stacked in this order to produce a laminate, the wound body or laminate produced is filled into each battery case, the lead bodies of the positive electrode and negative electrode are welded, and then an electrolyte is injected into the battery case and the opening of the battery case is sealed to complete the battery case. EXAMPLES

[0078] The present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto. Measurement methods used in the examples are as follows. [Measurement method] (1) Separator meltdown temperature A 50mm x 50mm separator, i.e., a polymer membrane, was cut out, and the sample was sandwiched between two stainless steel plates with a 12mm through hole in the center, and then sandwiched between two heating block plates with a 12mm through hole in the center on both sides. A tungsten carbide ball with a diameter of 9.5mm was placed in the through hole, and the heating block plate was heated at a rate of 5℃ / min. The temperature of the heating block plate was measured when the polymer membrane melted and the ball fell. The test was performed five times, and the average value was taken as the meltdown temperature (℃).

[0079] (2) Separator air permeability Measurements were performed using an Oken air permeability tester EGO-1T (manufactured by Asahi Seiko Co., Ltd.) in accordance with JIS P8117 (1998). The measurement limit for air permeability is 10,000 seconds. When the air permeability exceeds 10,000 seconds, the separator can be considered to have a substantially non-porous structure.

[0080] (3) Ionic conductivity (unit: S / cm) The polymer membrane was immersed in an electrolyte (1M LiTFSI ethylene carbonate (EC) / diethyl carbonate (DEC) = 1 / 1, manufactured by Mitsui Chemicals) for 8 hours, then removed once and placed on a SUS304 electrode to cover the electrode part, 5mL of electrolyte was dripped onto it, and the electrode was sandwiched between another SUS electrode to produce an electrode / polymer membrane / electrode laminate. The laminate was fixed with a silicon plate to prevent it from shifting, and an evaluation cell was produced.

[0081] The AC impedance of the prepared cell was measured at 25°C using an electrochemical tester model number SP-150 (manufactured by Biologic) under conditions of an amplitude of 10 mV and a frequency of 1 MHz to 10 mHz, and the resistance value was read from a graph plotted on a complex plane and substituted into the following formula to calculate the ionic conductivity. The measurement was performed five times, and the calculated average value was taken as the ionic conductivity.

[0082] σ=d1 / A R σ: Ionic conductivity (S / cm) d1: Thickness of polymer film (cm) (before immersion in electrolyte) A: Electrode area (cm 2 ) R: Resistance value (Ω).

[0083] (4) Contact angle between separator and organic solvent and its rate of change First, the polymer film, which is the separator, is left in an atmosphere of room temperature 23°C and relative humidity 65% ​​for 24 hours. Then, in the same atmosphere, 1 μL of two organic solvents, propylene carbonate (PC) and 1,2-dimethoxyethane (DME), are dropped onto the separator, and the contact angle after 10 seconds is measured five times for each using a contact angle meter DropMaster model number DM-501 (manufactured by Kyowa Interface Science Co., Ltd.). The average value of the three measured values ​​excluding the maximum and minimum values ​​of each of the five measured values ​​was taken as the contact angle of each organic solvent.

[0084] The contact angle was measured in the same manner one hour after the dropping, and the rate of change (%) from the contact angle 10 seconds after the dropping was evaluated using the following formula. (Contact angle 10 seconds after drop - Contact angle 1 hour after drop) / (Contact angle 10 seconds after drop) x 100 In addition, when comparing the contact angle 10 seconds after application with the contact angle 1 hour after application, the contact angle 10 seconds after application is often larger. Here, the rate of change (%) is calculated by subtracting the smaller contact angle from the larger contact angle so that the difference in contact angles is a positive value, and dividing the result by the contact angle 10 seconds after application.

[0085] (5) Area heat shrinkage rate of polymer film A sample of 50 mm × 50 mm was cut out. The length of each side in the longitudinal and transverse directions of the cut out sample was measured, and the longitudinal length L MD1 = 50 (mm), width direction length L TD1 = 50 (mm). The sample was placed in a hot air oven heated to 180°C for 60 minutes for heat treatment, and then allowed to cool. The dimensions of the shortest points in the longitudinal and transverse directions of the sample were measured, and the longitudinal length L MD2 (mm), width L TD2 The shrinkage rate was calculated based on the following formula: Area thermal shrinkage rate (%) = (L MD1 ×L TD1 -L MD2 ×L TD2 ) / L MD1 ×L TD1 ×100 Measurements were performed five times for each sample and averaged.

[0086] (6) Polymer logarithmic viscosity (unit: dl / g) The polymer was dissolved at a concentration of 0.5 g / dl in N-methylpyrrolidone (NMP) containing 2.5 wt% lithium bromide (LiBr), and the flow time was measured at 30° C. using an Ubbelohde viscometer. The flow time of a blank LiBr 2.5 wt% / NMP in which no polymer was dissolved was also measured in the same manner, and the viscosity η (dl / g) was calculated using the following formula.

[0087] η=[ln(t / t0)] / 0.5 t0: Blank flow time (S) t: sample flow time (S).

[0088] (7) Charge / discharge cycle characteristics The nonaqueous electrolyte secondary batteries prepared in each Example and Comparative Example were subjected to a charge-discharge cycle characteristic test according to the following procedure, and the discharge capacity retention rate was calculated. The charge-discharge cycle characteristic is one of the evaluation items for battery voltage and battery capacity, and a secondary battery having stable charge-discharge cycle characteristics, a discharge capacity retention rate that is less likely to decrease, and capable of maintaining the discharge capacity is considered to be good.

[0089] The cycle test consisted of one charge and discharge cycle, with the charge conditions being a constant current charge of 0.5C and 5V, and the discharge conditions being a constant current discharge of 0.5C and 2.8V, and the charge and discharge cycle was repeated 150 times at a temperature of 25°C. The discharge capacities obtained in the first cycle and the 150th cycle were measured, and the discharge capacity retention rate (%) was calculated using the following formula. (Discharge capacity at 150th cycle) / (Discharge capacity at 1st cycle) x 100 Tests were performed on five nonaqueous electrolyte secondary batteries prepared in each Example and Comparative Example, and the maximum and minimum discharge capacity retention rates were removed, and the average of the three measurement results was taken as the discharge capacity retention rate.

[0090] The discharge capacity retention rate was evaluated according to the following ranks: Secondary batteries with a discharge capacity retention rate of 60% or more, that is, ranks S, A, and B, are good. Discharge capacity retention rate is less than 60%: C Discharge capacity retention rate is 60% or more but less than 70%: B Discharge capacity retention rate is 70% or more but less than 75%: A Discharge capacity retention rate is 75% or more: S.

[0091] <Example 1> A separator and a non-aqueous electrolyte secondary battery were fabricated as follows. Table 1 shows the separator properties and the characteristics of the non-aqueous electrolyte secondary battery.

[0092] (Preparation of positive electrode) First, the positive electrode active material Li(Ni 0.5 Co 0.2 Mn 0.3 )O2 100 parts by mass, acetylene black 2 parts by mass as a conductive assistant, graphite 2 parts by mass as a conductive assistant, polyvinylidene fluoride (PVDF) 4 parts by mass as a binder (solid content supplied as N-methylpyrrolidone (NMP) solution), and maleic anhydride as an additive were mixed uniformly in NMP as a solvent to prepare a positive electrode mixture-containing paste. Next, the obtained positive electrode mixture-containing paste was intermittently applied to both sides of a positive electrode current collector made of aluminum foil with a thickness of 20 μm and dried, and then a calendar treatment was performed to adjust the thickness of the positive electrode mixture layer so that the total thickness was 169 μm, and the positive electrode was prepared by cutting it to a length of 504 mm and a width of 56 mm. Furthermore, a tab was welded to the exposed part of the aluminum foil of this positive electrode to form a lead part.

[0093] (Preparation of negative electrode) 100 parts by mass of graphite as the negative electrode active material, 1 part by mass of carboxymethyl cellulose (CMC) as the binder (solid content supplied as a 1% by mass aqueous solution), 3 parts by mass of styrene-butadiene rubber (SBR) (solid content supplied as a 3% by mass aqueous solution), and 5% by mass of carbon fiber as the conductive additive were dissolved in a solvent having a specific conductivity of 2.0 × 10 5 The paste containing the negative electrode mixture was mixed with ion-exchanged water having a resistivity of Ω / cm or more to prepare a paste containing the negative electrode mixture. Next, the obtained paste containing the negative electrode mixture was intermittently applied to both sides of a negative electrode current collector made of copper foil having a thickness of 16.5 μm, dried, and then calendered to adjust the thickness of the negative electrode mixture layer so that the total thickness was 148 μm, and cut to a length of 460 mm and a width of 58 mm to prepare a negative electrode. Furthermore, a tab was welded to the exposed part of the copper foil of this negative electrode to form a lead part.

[0094] (Preparation of electrolyte) A nonaqueous electrolyte having a HOMO energy of -11.5 eV or less was prepared as follows: 1.0 mol of lithium hexafluorophosphate (LiPF6) was dissolved in 1 L of a mixed solvent of ethylene carbonate (EC) and propylene carbonate (PC) in a volume ratio of 1:1 to prepare a mixed solution, and 2 parts by mass of vinylene carbonate (VC) was further added to 100 parts by mass of the mixed solution to prepare nonaqueous electrolyte A.

[0095] A nonaqueous electrolyte having a LUMO energy of 2 eV or more was prepared as follows: 1.0 mol of lithium hexafluorophosphate (LiPF6) was dissolved in 1,2-dimethoxyethane (DME) to prepare a mixed solution, and 2 parts by mass of vinylene carbonate (VC) was added to 100 parts by mass of the mixed solution to prepare nonaqueous electrolyte B.

[0096] (Preparation of separator) 4,4'-diaminodiphenyl ether was dissolved as a diamine in dehydrated N-methyl-2-pyrrolidone under a nitrogen stream and cooled to below 30°C. 2-chloroterephthaloyl chloride equivalent to 99 mol% of the total amount of diamine was added over 30 min while keeping the system at below 30°C under a nitrogen stream, and after the entire amount was added, the mixture was stirred for about 2 h to polymerize an aromatic polyamide. The obtained polymerization solution was neutralized with 97 mol% lithium carbonate and 6 mol% diethanolamine with respect to the total amount of acid chloride to obtain polymer solution A. The inherent viscosity η of the obtained polymer was 2.5 dl / g.

[0097] The obtained polymer solution was added with lithium salt bistrifluoromethylsulfonylimide lithium [LiN(CF3SO2)2] so that the molar ratio of lithium in the lithium salt to oxygen in the polymer was 0.2, and the mixture was stirred and degassed using a mixer (manufactured by THINKY, model number: AR-250) to obtain a uniform transparent solution. The obtained uniform mixed solution of polymer and lithium salt was applied in the form of a film on a glass plate as a support, and dried at a hot air temperature of 60°C until the polymer film had self-supporting properties, and then the polymer film was peeled off from the support. Next, the solvent and neutralized salt were extracted by introducing the mixture into a water bath at 25°C. Next, the water on the surface of the obtained water-containing polymer film was wiped off, and then the mixture was subjected to heat treatment for 1 min in a tenter chamber at a temperature of 180°C to obtain a polymer film with a thickness of 5 μm.

[0098] (Battery Assembly) In a dry atmosphere, the positive electrode, the negative electrode, and the separator were placed in a two-chamber cell (SB-100B manufactured by EC Frontier), and nonaqueous electrolyte A was injected into the positive electrode side and nonaqueous electrolyte B was injected into the negative electrode side to prepare a nonaqueous electrolyte secondary battery (lithium ion secondary battery) with a battery capacity of 3 mAh.

[0099] The properties of the polymer film of the obtained separator are shown in Table 1. The contact angle between the polymer film and propylene carbonate (PC) liquid 10 seconds after dropping was 110°, and the contact angle after 1 hour was 108°. The contact angle between the polymer film and 1,2-dimethoxyethane (DME) liquid 10 seconds after dropping was 105°, and the contact angle after 1 hour was 103°. The rate of change in the contact angle for both PC liquid and DME liquid was 2%.

[0100] The evaluation results of the obtained battery are shown in Table 1. The charge / discharge cycle characteristics were good, with rank S: 75% or more.

[0101] <Example 2> In preparing the separator, except that the lithium salt was changed to lithium trifluoromethasulfonate (LiCF3SO3), a nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 1. The evaluation results of the obtained battery are shown in Table 1.

[0102] <Example 3> A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that in the production of the negative electrode, the negative electrode mixture layer was changed to a lithium metal foil (thickness per side: 30 μm). The evaluation results of the obtained battery are shown in Table 1.

[0103] <Example 4> A secondary battery was produced in the same manner as in Example 1, except that in the preparation of the separator, lithium bistrifluoromethylsulfonylimide lithium [LiN(CF3SO2)2], which is a lithium salt, was added so that the molar ratio of lithium in the lithium salt to oxygen in the polymer was 0.1. The evaluation results of the obtained battery are shown in Table 1.

[0104] <Example 5> In the preparation of the separator, 4,4'-diaminodiphenyl ether was dissolved as a diamine in dehydrated N-methyl-2-pyrrolidone under a nitrogen stream and cooled to 30°C or lower. 2-chloroterephthaloyl chloride equivalent to 99.5 mol% relative to the total amount of diamine was added over 30 min while keeping the system at 30°C or lower under a nitrogen stream, and after the entire amount was added, the mixture was stirred for about 2 h to polymerize aromatic polyamide. The obtained polymerization solution was neutralized with 97 mol% lithium carbonate and 6 mol% diethanolamine relative to the total amount of acid chloride to obtain polymer solution B. The logarithmic viscosity η of the obtained polymer was 3.5 dl / g. A secondary battery was prepared in the same manner as in Example 1 except that the obtained polymer solution B was used. The evaluation results of the obtained battery are shown in Table 1.

[0105] <Example 6> A non-aqueous electrolyte solution having a HOMO energy of -11.5 eV or less was prepared by dissolving 1.0 mol of lithium hexafluorophosphate (LiPF6) in 1 L of ethylene carbonate (EC), and 2 parts by mass of vinylene carbonate (VC) was added to 100 parts by mass of the mixture to prepare non-aqueous electrolyte solution C. A secondary battery was prepared in the same manner as in Example 1 except that non-aqueous electrolyte solution C was used on the positive electrode side. The evaluation results of the obtained battery are shown in Table 1.

[0106] <Example 7> In the preparation of the separator, 4,4'-diaminodiphenyl ether was dissolved as a diamine in dehydrated N-methyl-2-pyrrolidone under a nitrogen stream and cooled to 30°C or lower. 2-chloroterephthaloyl chloride equivalent to 97 mol% of the total amount of diamine was added thereto over 30 min while keeping the system at 30°C or lower under a nitrogen stream, and after the entire amount was added, the mixture was stirred for about 2 h to polymerize aromatic polyamide. The obtained polymerization solution was neutralized with 97 mol% lithium carbonate and 6 mol% diethanolamine with respect to the total amount of acid chloride to obtain polymer solution C. The logarithmic viscosity η of the obtained polymer was 1.5 dl / g. A secondary battery was prepared in the same manner as in Example 1 except that the obtained polymer solution C was used. The evaluation results of the obtained battery are shown in Table 1.

[0107] <Comparative Example 1> A nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 1, except that both the positive electrode electrolyte and the negative electrode electrolyte were changed to nonaqueous electrolyte A. The evaluation results of the obtained battery are shown in Table 1.

[0108] <Comparative Example 2> A nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 1, except that both the positive electrode electrolyte and the negative electrode electrolyte were changed to nonaqueous electrolyte B. The evaluation results of the obtained battery are shown in Table 1.

[0109] <Comparative Example 3> The separator is a cellulose nonwoven fabric (thickness 40 μm, density 0.40 g / cm 3A non-aqueous electrolyte secondary battery was fabricated in the same manner as in Example 1, except that the non-woven fabric was made of 100% by mass of Lyocell fiber, which is a regenerated cellulose fiber, using a fourdrinier paper machine. The evaluation results of the obtained battery are shown in Table 1.

[0110] <Comparative Example 4> Except for changing the separator preparation to a simple polymer solution not containing a lithium salt, a non-aqueous electrolyte secondary battery was prepared in the same manner as in Example 3. The evaluation results of the obtained battery are shown in Table 1.

[0111] [Table 1]

[0112] From Table 1, Examples 1 to 7 contain nonaqueous electrolytes with two different solvent compositions, the contact angle of the organic solvent in the characteristics of the separator polymer film is 90° or more, and the nonaqueous electrolyte secondary battery shows good cycle characteristics. On the other hand, Comparative Examples 1 and 2 have one type of solvent composition in the nonaqueous electrolyte, and the cycle characteristics of the nonaqueous electrolyte secondary battery are insufficient. Comparative Example 3 has a contact angle of the organic solvent in the characteristics of the separator polymer film of less than 90°, and the nonaqueous electrolytes with two different solvent compositions cannot be separated, and the cycle characteristics of the nonaqueous electrolyte secondary battery are insufficient. Comparative Example 4 has an insufficient ion conductivity of the polymer film, and the cycle characteristics of the nonaqueous electrolyte secondary battery are insufficient.

Claims

1. A non-aqueous electrolyte secondary battery including a positive electrode, a negative electrode, a non-aqueous electrolyte, and a separator, The positive electrode active material is a lithium-containing transition metal oxide represented by the general formula LixMyOz (M is at least one element selected from the group consisting of Ni, Co, Mn, Al, Mg, and Mo, and the composition ratio satisfies 0.8≦x≦1.3, 0.5≦y≦2, and 1≦z≦4), The negative electrode active material includes one or more compounds selected from the group consisting of C-based compounds, Si-based compounds, Sn-based compounds, and metallic lithium, or metallic lithium; The nonaqueous electrolyte contains two kinds of solvents and is separated by the separator. The composition of the nonaqueous electrolyte in contact with the negative electrode side is different from the composition of the nonaqueous electrolyte in contact with the positive electrode side. The nonaqueous electrolyte contains a solvent and an electrolyte. The HOMO energy of the solvent of the nonaqueous electrolyte in contact with the positive electrode side is −11.5 eV or less, and the LUMO energy of the solvent of the nonaqueous electrolyte in contact with the negative electrode side is 2.0 eV or more. The separator has an air permeability of more than 10,000 seconds and an ionic conductivity of 1×10 -5 S / cm or more, and further, the contact angle between at least one surface of the separator and an organic solvent is 90° or more.

2. The separator has an air permeability of more than 10,000 seconds and an ionic conductivity of 1×10 -5 2. The nonaqueous electrolyte secondary battery according to claim 1, wherein the separator is a polymer film having a contact angle of 90° or more between at least one surface of the separator and a propylene carbonate liquid and a 1,2-dimethoxyethane liquid.

3. 3. The nonaqueous electrolyte secondary battery according to claim 1, wherein the rate of change in contact angle of the polymer film with an organic solvent after one hour is less than 10%.

4. 4. The nonaqueous electrolyte secondary battery according to claim 1, wherein the rate of change in contact angle of said polymer film with a propylene carbonate liquid and a 1,2-dimethoxyethane liquid after one hour is less than 10%.

5. 5. The nonaqueous electrolyte secondary battery according to claim 1, wherein the polymer film has an areal heat shrinkage rate of 10% or less after heat treatment at 180° C. for 60 minutes.

6. 6. The nonaqueous electrolyte secondary battery in accordance with claim 1, wherein the polymer film has a meltdown temperature of 300° C. or higher.

7. 7. The nonaqueous electrolyte secondary battery in accordance with claim 1, wherein the polymer film contains at least one polymer selected from the group consisting of aromatic polyamides, aromatic polyimides, and aromatic polyamideimides.

Citation Information

Patent Citations

  • Polymer secondary battery

    JP2002042874A

  • Lithium polymer secondary cell

    JP2002319434A

  • Battery

    JP2005216787A

  • Gelatinous electrolyte battery

    JP2007194104A

  • Separator for lithium ion secondary battery with process film

    JP2013211185A